Novel Algorithms And Fuzzy-Genetic Approach For Optimal Operation Of Electrical Distribution Systems - Krishna Prasad, Pamulapati (2005)
This research work is mainly concerned with development of algorithms for optimal operation of electrical distribution systems (EDS).